IMPROVEMENT METHOD OF GENE TRANSFER IN Kappaphycus alvarezii - St. Hidayah Triana; . Alimuddin; Utut Widyastuti; . Suharsono; Emma Suryati; Andi Parenrengi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Method of foreign gene transfer in red seaweed Kappaphycus alvarezii has been reported, however, li-mited number of transgenic F0 (broodstock) was obtained. This study was conducted to improve the method of gene transfer mediated by Agrobacterium tumefaciens in order to obtain high percentage of K. alvarezii transgenic. Superoxide dismutase gene from Melastoma malabatrichum (MmCu/Zn-SOD) was used as model towards increasing adaptability of K. alvarezii to environmental stress. The treat-ments were the culture media and recovery duration, and each treatment consisted of three replica-tions. The best method was co-cultivation using liquid media, then recovery was conducted in liquid media for 10 days. That treatment allowed higher transformation percentage (90%), regeneration effi-ciency (90%), putative bud efficiency (100%), number of buds and explants sprouted (100%) and transgenic explants (100%). The transgenic explants showed an amplification PCR product of Mm-Cu/Zn-SOD gene fragment, whereas the non-transgenic explants showed no amplification product.  All results revealed that suitable method of transgenesis for K. alvarezii has been developed. Keywords:       Agrobacterium tumefaciens, culture media, Kappaphycus alvarezii, recovery duration, transformation